2013
DOI: 10.1371/journal.pone.0072436
|View full text |Cite
|
Sign up to set email alerts
|

Joint Action Syntax in Japanese Martial Arts

Abstract: Participation in interpersonal competitions, such as fencing or Japanese martial arts, requires players to make instantaneous decisions and execute appropriate motor behaviors in response to various situations. Such actions can be understood as complex phenomena emerging from simple principles. We examined the intentional switching dynamics associated with continuous movement during interpersonal competition in terms of their emergence from a simple syntax. Linear functions on return maps identified two attrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 38 publications
0
37
0
Order By: Relevance
“…It has been reported that in offense and defense in Kendo, skilled persons often "take quick actions of offense and defense at a distant spatial timing", while non-skilled persons often "take slow actions of offense and defense at a near spatial timing" (Yamamoto, 2013). In the future, a discussion taking a temporal factor related to the offense and defense at a temporal timing into account in addition to the inter-personal distance from the opponent is necessary and expected.…”
Section: Bmimentioning
confidence: 99%
“…It has been reported that in offense and defense in Kendo, skilled persons often "take quick actions of offense and defense at a distant spatial timing", while non-skilled persons often "take slow actions of offense and defense at a near spatial timing" (Yamamoto, 2013). In the future, a discussion taking a temporal factor related to the offense and defense at a temporal timing into account in addition to the inter-personal distance from the opponent is necessary and expected.…”
Section: Bmimentioning
confidence: 99%
“…The first return (Lorenz) map was applied to the offensive and defensive maneuvers that occur during kendo matches as interpersonal competition [37]. variables constituted by interpersonal distance and its velocity.…”
Section: Return Map Reveals the Coordination Patterns During Interpermentioning
confidence: 99%
“…Red lines show attractors, blue lines show repellers, and cyan lines show intermittencies. Modified from[37].…”
mentioning
confidence: 99%
“…19 There are several authors and Japanese budō practitioners who employ perceptive-principles in their practice, in accordance with, for example, Yuasa's explanations. Interesting psycho-physiological studies were recently done by Ushiro (2008) and Yamato et al (2013). Perceptive-reaction principles in martial arts, such as kendō, are usually referred to as abrupt-switching-quick-response behavior (Yamato et al 2013: 1-9).…”
Section: Conclusion: Pattern-like Performativitymentioning
confidence: 99%
“…Interesting psycho-physiological studies were recently done by Ushiro (2008) and Yamato et al (2013). Perceptive-reaction principles in martial arts, such as kendō, are usually referred to as abrupt-switching-quick-response behavior (Yamato et al 2013: 1-9). jective of the paper was thus different, to show that modern Japanese martial arts inherited a lot of elements from the ancient styles, as well as that most of the movement structures used in modern budō actually descend from koryū budō heritage, either by direct lineage or by indirect influences, as in the example of aikidō and jūdō.…”
Section: Conclusion: Pattern-like Performativitymentioning
confidence: 99%